Kajian Biaya Penggantian Penyanggaan Kayu di Lubang Maju THC 04 di Tambang Bawah Tanah CV.Tahiti Coal, Sangkar Puyuh, Kecamatan Talawi, Kota Sawahlunto, Provinsi Sumatera Barat - Lulu Dwi Oktari; Heri Prabowo (Departemen Teknik Pertambangan FT UNP, 2022)
CV. Tahiti Coal is a mining industry company that exploits coal using underground and open pit mining methods. The company has 4 open pits that are still active, namely THC 02, Main Gate THC 03, Tail Gate THC 03 and Main Gate THC 04. In addition, there is also 1 open pit which temporarily stopped operating due to self-burning, namely THC 01. The mining method underground implemented by CV. Tahiti Coal is the Room and Pillar on THC 01, THC 02, THC 03. A pullback method is carried out, namely taking coal starting from the end which is taken from the bottom up (the previous branch line) leaving the top pillar 3 meters long. This taking is done 6 meters wide and interspersed with pillars 3 meters wide and so on up to the branch door. The coal that has been taken is assisted with the installation of supports and cribbing is carried out. At THC 04 using the room and pillar method, the direction of mining is planned in the direction of strike perpendicular to the dip which has a slope of 28-34 degrees. The buffer used by CV. Tahiti Coal is natural buffer and artificial buffer. Natural buffer is coal left behind with the aim of replacing pillars when making room and pillar opening holes. Meanwhile, artificial supports are supports formed from wood to hold the coal openings that have been taken. The type of wood used is first class wood.